The Development of Factors Promoting Success of Computer Merchandisers on Social Media - Tungeakachai, Kumpol; Punyaroj, Suthichai; Wasasisri, Noraset (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
This research aimed to study vendors’ opinion to marketing success factors in selling computer products on the social media; to study the level of success promotion factors of computer product sellers on the social media and to compare the customer opinions to the success promotion factors of the computer merchandisers on the social media. The samples were 5 computer sellers on social media sampled by purposive sampling method. They were members of the Facebook group named “Second-hand computer consignment Phitsanulok” who had posted equal or more than 10 messages in a week and 384 customers who bought the computers on the social media according to Cochran's formula. The research instruments for collecting data were in-depth interview and questionnaire. The statistics for analyzing data were frequency, percentage, mean, standard deviation, t-test and f-test for hypothesis testing, and content analysis. The results found that the vendors have opinion to marketing success factors in selling computer products at highest percentage which is the customer’s satisfaction and impressiveness aspect. In overview, the customers have opinions to the success promotion factors at high level. The customers with the different personal factors have no difference of the opinion to the success promotion factors.